Answer :
Answer:
T(n) = [n(n + 1)] ÷ 2
Step-by-step explanation:
Sequence = 1, 3, 6
First term = 1
Second term = first term + 2 = 3
Third term = second term + 3 = 6
From the sequence :
Each successive term is doubled together with an increment of '1', that is;
Term 'n' : n(n + 1)
Then, the total is divided by the term 'n'.
Therefore, the nth term is expressed as
T(n) = [n(n + 1)] ÷ 2
For instance,
n = 1
T(1) = [1(1 + 1)] ÷ 2
T(1) = 1
n = 3
T(3) = [3(3 + 1)] ÷ 2
T(3) = 12 ÷ 2 = 6
.......
Answer: The formula for the nth term of this sequence is
2^(n-1) + (n-1)
Step-by-step explanation: please find the attached file for the solution
